Biomechanical characterization of isolated epineurial and perineurial membranes of rabbit sciatic nerve. (May 2022) - Koppaka, Smruta; Hess-Dunning, Allison; Tyler, Dustin J.
Abstract: Design of interface devices for effective, long-term integration into neural tissue is dependent on the biomechanical properties of the nerve membranes. Within the peripheral nerve, the two relevant connective tissue layers for interfacing are the epineurium and perineurium. Previous work has reported the forces needed to penetrate the whole nerve, but the mechanical differences between epineurium and perineurium were not reported. Design of intraneural electrodes that place electrodes within the nerve requires knowledge of the mechanics of individual tissues. This study quantified the Young's moduli and ultimate strains of the perineurium and the epineurium separately. We also measured the forces necessary to penetrate each tissue in isolation. We used a custom-built microtensile testing device to measure the Young's modulus values. The measured Young's moduli of the epineurium and the perineurium was 0.4 ± 0.1 MPa and 3.0 ± 0.3 MPa, respectively. We also measured the force required for blunt and sharp stainless steel, 100 µm diameter probes to be inserted into isolated epineurial tissue and perineurial tissue at 2 mm/s. These data provide additional guidelines for selection of materials for long-term implants that best match the tissue properties. The results will guide neural interface design such that electrodes can be placed through either the epineurium alone or both the epineurium and perineurium.